2020
DOI: 10.21203/rs.3.rs-68828/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between tumor mutational burden and maximum standardized uptake value in 2-[18F]FDG PET (positron emission tomography) scan in cancer patients

Abstract: Purpose: Deriving links between imaging and genomic markers is an evolving field. 2-[18F]FDG PET/CT (18F-fluorodeoxyglucose Positron Emission Tomography- Computed Tomography) is commonly used for cancer imaging, with maximum standardized uptake value (SUVmax) as the main quantitative parameter. Tumor mutational burden (TMB), the quantitative variable obtained using next-generation sequencing on a tissue biopsy sample, is a putative immunotherapy response predictor. We report the relationship between TMB and SU… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, tumor volume and TLG were significant factors to predict high TMB. Although there have been previous studies to suggest a correlation between maximum SUV or other texture parameters and TMB [20,21], to the best of our knowledge, no previous study has demonstrated a relationship between volumetric parameters and TMB. This result is almost the same as a previous result suggesting that more genetic mutation corresponds with large tumor volume [31].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, tumor volume and TLG were significant factors to predict high TMB. Although there have been previous studies to suggest a correlation between maximum SUV or other texture parameters and TMB [20,21], to the best of our knowledge, no previous study has demonstrated a relationship between volumetric parameters and TMB. This result is almost the same as a previous result suggesting that more genetic mutation corresponds with large tumor volume [31].…”
Section: Discussionmentioning
confidence: 71%
“…A previous study investigated the correlation between PET-based radiomics and TMB in lung cancer [20]. Another pan-cancer analysis, including gastrointestinal cancer, showed an association between the standardized uptake value (SUV) on FDG PET/CT and TMB [21]. However, no prior study has attempted to predict TMB status using PET-based radiomics in CRC.…”
Section: Introductionmentioning
confidence: 99%